A Box of Darkness: Transforming the experience of existential loss (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
In the form of an episodic narrative case study, this article explores the transformation of an existential crisis into a form of awakening to a new lifeworld. Circling around a mysterious 'box of darkness', we navigate between modern poetry, early Buddhist texts and contemporary philosophy.
Keywords: Trauma; existential crisis; meaning vacuum; Buddhism; apocalypse; lifeworld; transformation